2009
DOI: 10.1089/ees.2007.0353
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Nitrogen and Phosphorus Removal in Pilot-Scale Vertical Subsurface Flow-Constructed Wetlands Using Polypropylene Pellets

Abstract: Removal of nitrogen and phosphorus is known to be somewhat problematic in vertical subsurface flow (VSSF)-constructed wetlands. In this pilot-scale study, two planted (Typha latifolia L.[cattail]) VSSF-constructed wetlands A (with polypropylene pellets) and B (without polypropylene pellets) and one unplanted control C (without polypropylene pellets) were designed to test the contribution of polypropylene pellets to nitrogen and phosphorus removal in eutrophic river water in Tianjin, China. The ranking order of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 33 publications
1
5
0
1
Order By: Relevance
“…A number of studies have indicated that addition of reactive Ca (CaO or Ca(OH) 2 ) is more efficient in improving the P adsorption capacity that Al and Fe addition [11,37,38]. In agreement with findings reported by Tanner et al [39] and Tang et al [40], the OM accumulation was highest in the inlet zone of the Sadowa wetland, but in some cases the OM content also increased in the outlet zone of the HSFCW (Figure 3). Contrary to our results, Tanner and Sukias [41] observed higher OM accumulation in the top layer (<10 cm) of planted and unplanted constructed wetlands.…”
Section: Discussionsupporting
confidence: 68%
“…A number of studies have indicated that addition of reactive Ca (CaO or Ca(OH) 2 ) is more efficient in improving the P adsorption capacity that Al and Fe addition [11,37,38]. In agreement with findings reported by Tanner et al [39] and Tang et al [40], the OM accumulation was highest in the inlet zone of the Sadowa wetland, but in some cases the OM content also increased in the outlet zone of the HSFCW (Figure 3). Contrary to our results, Tanner and Sukias [41] observed higher OM accumulation in the top layer (<10 cm) of planted and unplanted constructed wetlands.…”
Section: Discussionsupporting
confidence: 68%
“…Penggunaan tanaman air sebagai biofilter terbaik dari jenis eceng gondok Eichhornia crassipes (Tang et al, 2009;Vesely et al, 2011). Selain penggunaan tanaman air, upaya penurunan limbah N dapat dilakukan menggunakan probiotik.…”
Section: Pendahuluanunclassified
“…An alternative solution is to use some biofilm carrier, such as polypropylene pellets, to encourage (accelerate) biological nutrient removal. In contrast to the conventional shale-packed wetlands, the presence of polypropylene pellets would enhance removal of NH 4 -N, TN, SRP and TP by 13.38%, 8.90%, 9.29% and 8.25%, respectively (Tang et al 2009a). …”
Section: Constructed Wetlandsmentioning
confidence: 99%
“…Constructed wetlands are engineered systems that have been designed and constructed to utilize natural processes involving wetland vegetation, substrate and their associated microbial assemblages to assist in treating wastewater (Vymazal 2007;Tang et al 2009a). These systems take advantage of physical, chemical and biological processes occurring in natural wetlands, but do so within a semi-controlled environment.…”
Section: Constructed Wetlandsmentioning
confidence: 99%